2019
DOI: 10.1021/acssuschemeng.9b04443
|View full text |Cite
|
Sign up to set email alerts
|

Protic, Aprotic, and Choline-Derived Ionic Liquids: Toward Enhancing the Accessibility of Hardwood and Softwood

Abstract: A side-by-side comparison of softwood (pine) vs hardwood (eucalyptus) pretreatment using 3 protic, 3 aprotic, and 3 choline-derived ionic liquids (ILs) is proposed. While the protic ionic liquid 2-hydroxyethylammonium formate leads to alkali lignin dissolution at 30 °C after 1 h, the lack of interactions with the whole-cell wall limits the biomass disruption. On the contrary, the protic ionic liquid 1-methylimidazolium chloride produces a catalytic effect that extracts almost all of the hemicelluloses, and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Despite some studies done on the use of ammonium-based ILs including hydrogen bond-promoted lignin solubilization, absorption behavior of acid gases, as highly biodegradable solvents, etc., few reports have been made on the thermophysical properties of PILs, especially with anion lactate in the dilute region.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some studies done on the use of ammonium-based ILs including hydrogen bond-promoted lignin solubilization, absorption behavior of acid gases, as highly biodegradable solvents, etc., few reports have been made on the thermophysical properties of PILs, especially with anion lactate in the dilute region.…”
Section: Introductionmentioning
confidence: 99%
“…14 To overcome cost and biocompatibility issues, certain choline-based aprotic ILs were investigated and have been demonstrated for compatibility with both enzymes and microbes, allowing the transition towards a one-pot reaction system where all the steps of the process are carried out in a single vessel without any separations. 17 [Ch][Lys] has been effectively used and achieves high cellulose to glucose conversion yields in grasses and more recently in hardwoods and softwoods. 18 To date, we have demonstrated that [Ch][Lys] is effective at promoting high glucose yields in switchgrass (96.5%) and corn stover (>80%).…”
Section: Introductionmentioning
confidence: 99%
“…24 Despite many reports on agricultural wastes and grasses, there are few reports on hardwood waste pretreatment using ionic liquids. 25,26 These wood wastes can be an economic source of biorenery products. The abundance of Acacia hardwood and its fast growing nature make wastes of this hardwood a viable candidate for biomass processing in countries like Pakistan.…”
Section: Introductionmentioning
confidence: 99%